Intestinal organoid modeling: bridging the gap from experimental model to clinical translation - Liu, Taotao; Li, Xiaoqi; Li, Hao; Qin, Jingjing; Xu, Hui; Wen, Jun; He, Yaqin; Zhang, Cao (Frontiers in Oncology, 2024)
The 3D culture of intestinal organoids entails embedding isolated intestinal crypts and bone marrow mesenchymal stem cells within a growth factor-enriched matrix gel. This process leads to the formation of hollow microspheres with structures resembling intestinal epithelial cells, which are referred to as intestinal organoids. These structures encompass various functional epithelial cell types found in the small intestine and closely mimic the organizational patterns of the small intestine, earning them the name “mini-intestines”. Intestinal tumors are prevalent within the digestive system and represent a significant menace to human health. Through the application of 3D culture technology, miniature colorectal organs can be cultivated to retain the genetic characteristics of the primary tumor. This innovation offers novel prospects for individualized treatments among patients with intestinal tumors. Presently established libraries of patient-derived organoids serve as potent tools for conducting comprehensive investigations into tissue functionality, developmental processes, tumorigenesis, and the pathobiology of cancer. This review explores the origins of intestinal organoids, their culturing environments, and their advancements in the realm of precision medicine. It also addresses the current challenges and outlines future prospects for development.